Expressão gênica de membros do sistema IGF em óocitos e células do cumulus provenientes de vacas de diferentes genótipos leiteiros - Lopes, Asafe Costa (2016)
In last years it has been noted increasing utilization of in vitro embryo production (IVEP) in dairy breeds production. In this context, is known that differences in the number and development potential of oocytes between European (Bos taurus taurus) and Zebu (Bos indicus taurus) cows affect extremely the efficiency and economic viability of IVEP. Since, insulin-like growth factor (IGF) system is related to developmental capacity of oocytes, the aim of this study was to quantify mRNA abundance of IGF system members in cumulus oocytes complex (COCs) from Gir, Holstein and 1/2 Holstein x 1/2 Gir donor cows. Pools of 30 immature COCs from Gir (n=4 pools), Holstein (n=4 pools) and 1/2 Holstein x 1/2 Gir donor cows (n=4 pools) were obtained by ovum pick-up on farms in the southern region of Minas Gerais state, Brazil. Oocytes and cumulus cells were mechanically separated and stored in liquid nitrogen. Only selected COCs were analyzed with homogeneous cytoplasm and surrounded by, at least, three layers of compact cumulus cells were selected for the experiment. Total RNA was extracted from pools of 30 oocytes and their respective cumulus cells using the RNeasy® kit (Qiagen). The investigation of target genes (IGF1 and IGF2), their receptors (IGFR1 and IGFR2), as well as IGF binding proteins (IGFBP2, IGFBP4), and pregnancy-associated plasma protein-A (PAPPA) was assessed by real time RT-PCR using Power SYBR® green master mix (Applied Biosystems) and normalized by Cyclophilin (CYC-A). Relative quantification of mRNA abundance was determined using the ΔΔCt method with correction by Pfaffl’s equation. Effects of breeds on the expression of target genes in oocytes and cumulus cells were tested by ANOVA and means were compared by Tukey-Kramer HSD test. Differences were considered significant when P<0.05. In oocytes, mRNA encoding IGFR1 was higher in Gir compared to Holstein and 1/2 Holstein x 1/2 Gir animals. The relative mRNA abundance of IGF2, IGFR2 and IGFBP4 was higher in the cumulus cells of Holstein donor compared to Gir cows. The mRNA abundance of PAPPA was higher in cumulus cells and oocytes in Gir and 1/2 Holstein x 1/2 Gir donor cows compared to the Holstein donors. No differences on mRNA abundance of IGF1, IGF2, IGFR2, IGFBP2 and IGFBP4 in oocytes and IGF1, IGFR1 and IGFBP2 in cumulus cells were demonstrated among different breeds. In conclusion, the higher PAPPA mRNA abundance in oocyte and cumulus cells from Gir and 1/2 Holstein x 1/2 Gir donors associated with low expression of IGFBP4 in cumulus cells of these breeds, suggest more efficient degradation of IGFBPs, which results in greater bioavailability of IGF in Gir and crossbred (1/2 Holstein x 1/2 Gir) COCs when compared to the Holstein immature COCs.